Metafora Konseptual dalam Iklan Wardah "Beauty Moves You" (Tinjauan Semantik Kognitif) - Nur Rizka Laila; Sarah Sahilah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to identify and analyze the types of conceptual metaphors in Wardah’s “Beauty Moves You” advertising texts using a cognitive semantic approach. The research focuses on the mapping between the source domain and the target domain in each metaphorical phrase, based on the theory proposed by Lakoff and Johnson (1980). This study employs a descriptive qualitative method using listening and note-taking techniques. The data were collected from Wardah's official advertising videos published on the YouTube platform, which were then transcribed and analyzed based on the classification of three types of conceptual metaphors: structural, ontological, and orientational. The results show that seven metaphorical phrases were identified in the advertisement text, reflecting the concept of beauty as an active force, a social driver, and an agent of transformation. Five phrases were categorized as structural metaphors, four as ontological metaphors, and three as orientational metaphors, with some phrases falling into more than one category. The findings suggest that Wardah’s advertisements do not merely promote products, but also construct new meanings of women’s beauty, empowerment, and spirituality through metaphorical expressions. Keywords: Conceptual Metaphor; Lakoff and Johnson; Wardah Advertisement; Cognitive Semantics; Metaphor.